Sustainable healthcare lean management implementations in outpatient healthcare: a systematic literature review - Caterina Pozzan; Chiara Pamich; Anna Tiso; Chiara Verbano (International Journal of Quality & Reliability Management, 2026)
Purpose Healthcare lean management (HLM) is a managerial approach widely adopted in hospitals to reduce waste and improve process performance. Despite its potential to support sustainable care quality, its adoption in territorial healthcare is still in its early stages. This aspect is particularly relevant for primary and secondary low-complexity outpatient healthcare (LCOH), which often represents the first point of access to national healthcare systems and has a crucial role in the aging society. Given the relevance of this topic and the limited literature available, the current structured literature review aims to analyze HLM implementations in LCOH to support sustainable care quality. Design/methodology/approach A structured literature review was conducted on HLM implementations within LCOH, analyzing the care quality goals pursued, managerial and organizational activities, tools and practices employed, outcomes achieved, encountered sustainability barriers and facilitators. Findings The analysis highlights the importance of comprehensively addressing care quality to effectively implement HLM in LCOH, identifying specific barriers and facilitators to foster sustainable care quality. It underscores the limited evidence on HLM implementations within LCOH, especially considering public and European healthcare systems. Moreover, a lack of implementations addressing comprehensive care quality aspects was identified, highlighting limited evidence on care quality sustainability. Originality/value From an academic point of view, this study broadens the knowledge of HLM implementations outside hospital boundaries, addressing care sustainability within the territorial context. Moreover, considering managerial aspects, it provides valuable insights for healthcare organizations that aim to implement HLM, guaranteeing project completion and sustained improvement over time.